Dynamical Modulation of Wintertime Synoptic-Scale Cyclone Activity over the Japan Sea due to Changbai Mountain in the Korean Peninsula - Hiroyuki Shimizu; Ryuichi Kawamura; Tetsuya Kawano; Satoshi Iizuka (Advances in Meteorology)
The dynamical impact of the Changbai Mountain Range in the Korean Peninsula on the extratropical cyclone activity over the Japan Sea in early winter is examined using the Weather Research Forecasting model. We have conducted two independent long-term integrations over 15 winter months (December only) from 2000 to 2014 with and without modified topography. The results show that the Changbai Mountain Range plays a vital role in increasing cyclone track frequency, low-level poleward eddy heat flux, and the local deepening rate over the Japan Sea through enhancement of the lower-tropospheric baroclinic zone (LTBZ). This mountain range gives rise to activation of the synoptic-scale cyclone activity over that region. From our case study on three typical cyclones, it is found that mesoscale structures in the vicinity of a cyclone’s center are dynamically modulated when it passes through the LTBZ and that cyclogenesis is triggered around that zone. A vorticity budget analysis shows that the stretching term relevant to enhanced low-level convergence plays a dominant role in intensifying cyclonic vorticities. We confirmed that the composite features of the three typical cases are consistent with the statistical ones of the dynamical modulation of the Changbai Mountain on synoptic-scale cyclone activity.